OPTIMALISASI KLASIFIKASI KOLEKSI MUSEUM KEKHATUAN SEMAKA SEBAGAI SUMBER BELAJAR - Risma Margaretha Sinaga; Sudjarwo; Muhammad Mona Adha (Jurnal Visipena, 2022)
The purpose of this study is to provide a brief policy for the historical learning method on the theme of historical sources that provides a more meaningful learning experience for students. This research is based on field observations by looking at the reality that there are still problems in learning history in schools. Problems in learning history at school include the strong stigma attached to subjects that are full of rote, dry, and even boring. Plus other problems that exist in the learning process is still teacher-centered. The lack of innovation in learning history makes students finally lose their passion in learning history. The use of the museum as a learning resource in history learning and as an introduction effort related to the conservation of historical collection objects at the Semaka Kekhatuan Museum, is a form of effort in maintaining and conserving the collections at the Semaka Kekhatuan Museum so that it remains sustainable, and its existence is maintained other than as a tourism but as a source of learning that can be used for various purposes. The use of museums as a learning resource is actually able to provide a positive stimulus in history learning. This research uses qualitative method with descriptive research type. The components that are the focus of this research are: 1) Classification of the Kekhatuan Semaka Museum Collection which can be used as a learning resource, 2) Teachers' efforts in utilizing museum collections as a source of history learning, and 3) How are conservation efforts towards museum collections. Data collection techniques using observation techniques, interviews, and document data analysis. Based on the results and discussion, it can be concluded that the Kekhatuan Semaka Museum can be categorized as a source of history learning for students. Classification of collections into 9 types including geology, biology, ethnography, archeology, numismatics, philology, ceramics, fine arts and technology becomes an important learning point that can be associated with conservation efforts of historical heritage. Abstrak Tujuan penelitian ini adalah memberikan brief policy (kebijakan singkat) bagi metode pembelajaran sejarah pada tema sumber sejarah yang memberikan pengalaman belajar peserta didik agar lebih bermakna. Penelitian ini didasarkan atas pengamatan dilapangan dengan melihat realita bahwa pembelajaran sejarah di sekolah masih ditemukan masalah. Permasalahan dalam pembelajaran sejarah di sekolah diantaranya masih tertanam kuatnya stigma tentang mata pelajaran yang penuh hafalan, kering, bahkan membosankan. Ditambah permasalahan lain yang ada dalam prosesnya pembelajaran masih berpusat pada guru. Minimnya inovasi dalam pembelajaran sejarah membuat siswa akhirnya kehilangan gairah dalam belajar sejarah. Pemanfaatan museum sebagai sumber belajar dalam pembelajaran sejarah dan sebagai upaya introduksi terkait upaya koservasi benda-benda koleksi sejarah di Museum Kekhatuan Semaka, adalah bentuk dari upaya dalam menjaga dan mengkonservasi benda-benda koleksi di Museum Kekhatuan Semaka agar tetap lestari, dan terawat eksistensinya selain sebagai pariwisata melainkan sebagai sumber belajar yang dapat dimanfaatkan dalam berbagai keperluan. Pemanfaatan museum sebagai sumber belajar sebetulnya mampu memberikan stimulus positif dalam pembelajaran sejarah. Penelitian ini menggunakan metode kualitatif dengan jenis penelitian deskriptif. Komponen-komponen yang menjadi fokus penelitian ini, yaitu: 1) Klasifikasi Koleksi Museum Kekhatuan Semaka yang dapat dimanfaatkan sebagai sumber belajar, 2) Upaya guru dalam memanfaatkan koleksi museum sebagai sumber belajar sejarah, dan 3) Bagaimana upaya konservasi terhadap benda-benda koleksi museum. Teknik pengumpulan data menggunakan teknik observasi, wawancara, dan analisis data dokumen. Berdasarkan hasil dan pembahasan dapat disimpulkan bahwa Museum Kekhatuan Semaka dapat dikategorikan sebagai sumber belajar sejarah bagi siswa. Pengklasifikasian koleksi menjadi 9 jenis diantaranya geologika, biologika, etnografika, arkeologika, numismatika, filologika, keramologika, senirupa dan teknologika menjadi poin penting pembelajaran yang dapat dikaitkan dengan upaya konservasi peninggalan-peninggalan sejarah.